Identification and characterization of sirtuin enzymes in cestodes and evaluation of sirtuin inhibitors as new cestocidal molecules - Vaca, Hugo Rolando (2022)
Anti-parasitic treatment of neglected tropical diseases caused by cestodes such as echinococcosis and cysticercosis relies on a small number of approved anthelmintic drugs. Furthermore, the treatment is usually prolonged and often partially effective and not well tolerated by some patients. Therefore, the identification of novel drug targets and their associated compounds is critical. In this study, we identified and characterised sirtuin enzymes in cestodes and evaluated the cestocidal potential of sirtuin inhibitors as new cestocidal molecules. Sirtuins are a highly conserved family of nicotinamide-adenine dinucleotide-lysine deacylases involved in multiple cellular functions. Here, we described the full repertoire of sirtuin-encoding genes in several cestode species. We identified six sirtuin-encoding genes that were classified into sirtuins Class I (SIRT1, SIRT2, and SIRT3), Class III (SIRT5), and Class IV (SIRT6 and SIRT7). In Echinococcus spp., sirtuin genes showed transcriptional expression throughout several developmental stages, sirtuin 2 (SIRT2) being the most expressed. To evaluate the potential of sirtuin inhibitors as new cestocidal molecules, we determined the in vitro effect of several Class I sirtuin inhibitors by motility assay. Of those, the selective SIRT2 inhibitor Mz25 showed a strong cestocidal activity in Mesocestoides vogae (syn. Mesocestoides corti) tetrathyridia at various concentrations. The Mz25 cestocidal activity was time- and dose-dependent with a half-maximal inhibitory concentration value significantly lower than that of albendazole. Additionally, Mz25 induced extensive damage in the general morphology with marked alterations in the tegument and ultrastructural features. By homology modelling, we found that cestode SIRT2s showed a high conservation of the canonical sirtuin structure as well as in the residues related to Mz25 binding. Interestingly, some non-conservative mutations were found on the selectivity pocket (an Mz25-induced structural rearrangement on the active site), which represent a promising lead for developing selective cestode SIRT2 inhibitors derived from Mz25. Nevertheless, the Mz25 molecular target in M. vogae is unknown and remains to be determined. This report provides the basis for further studies of sirtuins to understand their roles in cestode biology and to develop selective sirtuin inhibitors to treat these neglected tropical diseases.